Persepsi Penggemar K-Pop (Korean Pop) Tentang Aplikasi Weverse Sebagai Media Komunikasi Penggemar dan Idolanya - Titik Layli Hirwiza; Faizal Hamzah Lubis (Universitas Muhammadiyah Sumatera Utara, 2023)
The purpose of this study is to find out how K-Pop fans perceive the Weverse application as a communication medium. The research method used in this study is a qualitative descriptive method, namely a method that describes a population or condition systematically and accurately which in its implementation will analyze and collect data that is not numbers. Data analysis techniques from this study used interviews and documentation. The results of the study show that the Weverse application was designed by HYBE Corporation to be a medium of communication for fans and idols who are members of HYBE Labels and from outside. The Weverse application is the most convenient choice of communication media for fans because the features provided are very easy to understand. However, there are still a number of deficiencies that the Weverse application still has which it is hoped that in the future the management can consider these to improve and add to some of these deficiencies